Answer:
x = 72
Step-by-step explanation:
[tex]\frac{-7}{9}x-\frac{5}{36}x+\frac{1}{4}x=-48[/tex]
Step 1: Simplify both sides of the equation.
[tex]\frac{-7}{9}x-\frac{5}{36}x+\frac{1}{4}x=-48[/tex]
[tex]\frac{-7}{9}x+\frac{-5}{36}x+\frac{1}{4}x=-48[/tex]
[tex](\frac{-7}{9}x+\frac{-5}{36}x+\frac{1}{4}x)=-48[/tex] (Combine Like Terms)
[tex]\frac{-2}{3}x=-48[/tex]
[tex]\frac{-2}{3}x=-48[/tex]
Step 2: Multiply both sides by [tex](\frac{3}{-2} )[/tex]
[tex](\frac{3}{-2})*(\frac{-2}{3}x)=(\frac{3}{-2})*(-48)[/tex]
[tex]x=72[/tex]
Therefore, [tex]x=72[/tex] is your final answer.